International Year of Planet Earth 3. Groundwater Sustainable Devlopment in Canada — Emergin Issues - Rivera, Alfonso (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2008)
SUMMARY Development of sustainable groundwater management in Canada requires an integrated approach, including scientific knowledge and managerial and institutional issues. The priority areas that must be considered to assure the sustainable use of groundwater include factors related to groundwater availability and use; these are based on aquifer knowledge (hydrogeological maps, water budgets), as well as social (water demands), political (water laws and regulations), economical, and environmental issues (ecosystem needs). Outside of the Permafrost Shield, groundwater is ubiquitous in most of the landmass of Canada but its distribution (quantity and quality) is only well known in scattered parts of the country. To sustain groundwater supplies in urban and rural areas, the management of groundwater resources should be supported by strong sciencebased programs with scientific knowledge of groundwater availability, vulnerability and sustainability and should be incorporated with water laws and regulations. A case study of an aquifer located in the province of Québec reveals the consequences of the use of groundwater beyond sustainable pumping rates. This case study involved detailed assessment of the aquifer and 3D numerical simulations of the current and predictive scenarios of groundwater withdrawals. A synthesis of the current knowledge of groundwater resources in the world and in Canada as well as the state-ofthe-art of the groundwater sciences, future research activities and other emerging issues with respect to the environment, society and policy, complete this overview.